2017
DOI: 10.21037/jtd.2017.03.21
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence of pulmonary hypertension in patients with obesity hypoventilation syndrome: a prospective observational study

Abstract: PH is very common among patients with OHS who have been referred to sleep disorders clinics. PH should be considered in the regular clinical assessment of all patients with OHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…; Almeneessier et al . ; Kaw, ). In addition, we will not discuss details about aminorex fumarate, fenfluramine and dexfenfluramine in this review.…”
Section: Vascular Function In Obesitymentioning
confidence: 99%
“…; Almeneessier et al . ; Kaw, ). In addition, we will not discuss details about aminorex fumarate, fenfluramine and dexfenfluramine in this review.…”
Section: Vascular Function In Obesitymentioning
confidence: 99%
“…Obesity‐hypoventilation syndrome occurs with alveolar hypoventilation during sleeping and daytime 1,2 . Obesity was associated with risk of venous thromboembolic disease 3 .…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition to left heart failure, coronary heart disease and systemic hypertension, pulmonary hypertension (PH) is an important feature in OHS. [7][8][9] However, robust data on PH in OHS, particularly its prevalence in patients with NPPV, are scarce. [9][10][11][12][13] In a previous work, we determined PH by right heart catheterization (RHC) in a prospective cross-sectional study of clinically stable OHS patients, treated with NPPV for at least 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has been hypothesised that PH in OHS is predominately linked to pulmonary vascular response to hypercapnia and hypoxia, 15 although pulmonary artery pressure obviously cannot be normalised in all patients despite NPPV therapy. [8][9][10]13,14 Surprisingly, PH has not yet been systematically explored in a larger cohort of patients with OHS with regard to long-term outcome, although Masa and coworkers recently showed that in patients with OHS and concomitant severe OSA, NPPV led to a reduction of systolic pulmonary artery pressure and left ventricle diastolic dysfunction. 13 Based on these considerations and the known impact of PH in other respiratory and/or pulmonary diseases, 16 we hypothesised that PH is a major prognostic factor in OHS and related to subjective outcome measures.…”
Section: Introductionmentioning
confidence: 99%